Structural Relationship Model of Insecure Attachment Styles and Suicidal Ideation: The Mediating Role of Mentalization Deficits and Emotion Regulation Deficits - Hashemi, Touraj; Hejazifar, SeyedMahdi (International Journal of Education and Cognitive Sciences, 2026)
Purpose: The present study aimed to determine the structural relationship model between insecure attachment styles and suicidal ideation among university students, with the mediating roles of mentalization deficits and emotion regulation deficits.Methods and Materials: In terms of purpose, this study was applied research, and in terms of methodology, it employed a descriptive-correlational design based on structural equation modeling. The statistical population consisted of all students of the University of Tabriz during the 2024–2025 academic year. From this population, 378 participants were selected using cluster random sampling. Data were collected using the Attachment Styles Questionnaire (Hazan & Shaver, 1987), the Emotion Regulation Questionnaire (Gross & John, 2003), the Beck Scale for Suicide Ideation (Beck, 1991), and the Mentalization Questionnaire (Dimitrijević et al., 2017). Data were analyzed using Pearson’s correlation coefficient and structural equation modeling through SPSS-18 and AMOS-22 software.Findings: The results indicated that insecure attachment styles, emotion regulation deficits, and mentalization deficits were significant positive predictors of suicidal ideation (p < .05). Furthermore, the structural model demonstrated a satisfactory fit, and the study variables collectively explained 69% of the variance in suicidal ideation. Emotion regulation deficits and mentalization deficits also played significant mediating roles in the relationship between insecure attachment styles and suicidal ideation (p < .05).Conclusion: The findings suggest that insecure attachment styles increase students’ vulnerability to suicidal thoughts by weakening mentalization capacities and disrupting emotion regulation mechanisms.